Pengembangan Produk Wedang Uwuh Bunga Turi (Sesbania grandiflora) Sebagai Sarana Branding Desa Wisata Kebonagung, Imogiri, Bantul - Septriani, Nur Indah; Arsanti, Faulindra Dita; Sholihati, Febina; Ahmad, Datu Maulana (Direktorat Pengabdian kepada Masyarakat, 2023)
Kebonagung tourist village offers a variety of tourist destinations ranging from agricultural education, traditions, to crafts. As a complement, the manager of the tourist village provides a welcoming drink for visiting tourists. However, there has not been a welcoming drink and typical souvenirs from the Kebonagung Village. The dedication aims to create product processing innovations from local resources. The KKN-PPM UGM from Imogiri unit took the initiative to develop the Vegetable Hummingbird Wedang Uwuh product. This dedication begins with a preliminary survey, then continues with the process of developing wedang uwuh products using the drying method. At the end of the dedication activity, socialization was carried out regarding the production process of Vegetable Hummingbird Wedang Uwuh and a survey has done through interviews to determine the level of success of the dedication activity. Making Vegetable Hummingbird Wedang Uwuh begins with washing the ingredients thoroughly, sun drying the ingredients, drying the ingredients using an oven at 50°C, then packing the dry ingredients in tea bags to make the product easier to consume. The product is also repackaged in a paper pouch by paying attention to the packaging design so that a product prototype is produced. Vegetable Hummingbird Wedang Uwuh product development program is quite successful. This is proven by the results of interviews regarding the level of participants' understanding of the techniques for processing and packaging designs for Vegetable Hummingbird Wedang Uwuh. The commitment of local SME actors also supports the goals of sustainable development or Sustainable Development Goals (SDGs).